(untitled) (European Bison Conservation Newsletter, 2009)
In 1949 professor Kazimierz Krysiak, as excellent anatomist and an outstanding scientist, created The Centre the European Bison Anatomy Research within the Department of Animal Anatomy at the Warsaw University of Life Sciences (SGGW). Over the last 60 years intensive anatomical examination of the species has been the subject of study carried out in the Centre. The results are fundamental for research in areas such as physiology, genetics, breeding, pathology and protection. 124 papers have been published in the field of the European bison’s anatomy. Among those there are 5 postdoctoral dissertations and 17 doctoral thesis. The remaining 102 studies have been published in recognized scientific magazines: both domestic and foreign. Many of them have been created in collaboration with other scientific institutions; mainly with the Institute of Mammal Research Polish Academy of Sciences in Bialowiez˙a. The publications cover all areas of anatomy. Most of them analyze osteological problems. The results of the research carried out in the Centre have significantly improved the knowledge of the European bison’s anatomy in comparison to other species domestic animals.